2003
DOI: 10.1002/jcla.10077
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microplate ELISA for circulating E‐selectin: assay characterization, comparison with a commercial kit, wand establishment of normal reference values

Abstract: E-selectin, an adhesion molecule, is detectable in the blood. Serum levels of E-selectin can be a prognostic indicator for various malignancies. We developed a microplate enzyme-linked immunosorbent assay (ELISA) for the detection of circulating E-selectin by coating the microwell with monoclonal anti-E-selectin. We incubated the specimen and the biotinylated detecting antibody simultaneously, and used HPR-conjugated streptavidin to generate a signal for quantification. The assay has a sensitivity of 3.8 ng/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Most markers were measured with in-house developed enzyme linked immunosorbent assay (ELISA) including C-reactive protein (CRP) with a highly sensitive assay (13), serum amyloid A (SAA) (14) adhesion molecules (15,16), uMA (17), 8-hydroxydeoxyguanosine (8-OHdG) (18), interleukin-6 (IL-6) (19), and 3-nitrotyrosine (3NT) (20). All in-house kits have been compared with a commercial kit with good to excellent correlation.…”
Section: Assaysmentioning
confidence: 99%
“…Most markers were measured with in-house developed enzyme linked immunosorbent assay (ELISA) including C-reactive protein (CRP) with a highly sensitive assay (13), serum amyloid A (SAA) (14) adhesion molecules (15,16), uMA (17), 8-hydroxydeoxyguanosine (8-OHdG) (18), interleukin-6 (IL-6) (19), and 3-nitrotyrosine (3NT) (20). All in-house kits have been compared with a commercial kit with good to excellent correlation.…”
Section: Assaysmentioning
confidence: 99%
“…E-selectin is mainly located in vascular endothelial cells, and the expression of which can be obviously induced by inflammatory cytokine especially in cerebrovascular endothelial cells. However, the serum concentration of which will not upregulate at all [11].…”
Section: Discussionmentioning
confidence: 98%
“…E-selectin is a kind of glycoprotein whose molecular weight is 115KD, which exists in endothelial cells. Pro-inflammatory cytokines such as interleukin, tumor necrosis factor and interferon have stimulatory effects on the synthesis of E-selectin [11]. Studies have revealed that cerebrovascular endothelial cells under normal condition barely have expression of E-selectin.…”
Section: Introductionmentioning
confidence: 99%
“…All of these in-house kits have been compared with commercial kits with good to excellent correlation, including CRP (20), adhesion molecules (21,22), IL-6 (23), uMA (24), and homocysteine (Hcy) (25). Uric acid (UA) was determined by a Hitachi 7600-210 autoanalyzer (Hitachi, Tokyo, Japan).…”
Section: Assaysmentioning
confidence: 99%